If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 2 + -3n Solving 11 = 2 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 11 + 3n = 2 + -3n + 3n Combine like terms: -3n + 3n = 0 11 + 3n = 2 + 0 11 + 3n = 2 Add '-11' to each side of the equation. 11 + -11 + 3n = 2 + -11 Combine like terms: 11 + -11 = 0 0 + 3n = 2 + -11 3n = 2 + -11 Combine like terms: 2 + -11 = -9 3n = -9 Divide each side by '3'. n = -3 Simplifying n = -3
| 5x=(33/34)+3 | | 3+8n= | | 15x^3-50x^2-40x=0 | | n/2-9=2 | | 7x-4=5x+6+2x | | 2/5x=22 | | 3-x=2x-3/2 | | 6(4+p)=12 | | -6[m+6]=132 | | 4=h(6h-2)(3h-2) | | h=-16t^2+60t+8 | | 3[x-5]=-6 | | 3x+5=80 | | 6x+4(-x+8)=4-3(x+5) | | x/5-8=7 | | -1/3x-4=12 | | 7.5(x-3)=-0.5x+25.5 | | -4/3x-3=-5/3-2x | | 125=5x^2 | | x/5-5=-9 | | 4a+a=40 | | -14m-10=32 | | -1/2c+3=-5/6 | | ((1/9)(2m-16))=((1/3)(2m+4)) | | -6d-9d+5d=60 | | -5/6-1/2 | | 6x+5=2x+5 | | 6(t-7)=9(t-4) | | 5x*x= | | 22/2/5 | | 1/2(5-2n)=n/2 | | 13t-3t=-60 |